1978
DOI: 10.1172/jci109157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Rate of H+ Transport and Pathways of Glucose Metabolism by Turtle Urinary Bladder

Abstract: A B S T R A C T The urinary bladder of the fresh-water turtle acidifies its contents by actively transporting H+ ions across the luminal membrane. It is known that the H+ transport system is dependent upon oxidative metabolism and the substrate glucose; however, the specific biochemical events resulting in H+ translocation have not been identified.This study examines the relationship between active H+ transport and a specific oxidative pathway ofglucose metabolism, the pentose phosphate shunt. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…DIES and LOTSPEICH(1967)proposed,following an earlier suggestion by BRODSKY and CARASQUER(1952),that NADPH formed via the hexose monophosphate shunt might provide protons for acidification.Although they accepted the strong evidence favoring carbon dioxide as the source of most of the hydrogen ions secreted,they believed that such evidence did not preclude the existence of an additional secretory mechanism.In support of their theory they found that the level of glucose-6-phosphate dehydrogenase was elevated in the renal cortex of acidotic animals,but not in their livers.Their idea received further support from experiments by NORBY and SCHWARTZ(1978),who measured the rate of acidification by turtle urinary bladders.The turtle bladder acidifies its contents in vitro by a process that requires metabolism.Norby and Schwartz examined several different situations in which the rate of acidification was altered and found that the rate of acidification correlated with the rate of glucose metabolism via the hexose monophosphate shunt,but not with the rate of glycolysis. Schwartz et al(unpublished observation)measured glucose-6-phosphate dehydrogenase activity in isolated cortical collecting ducts and found that it was increased more than three-fold in tubules from rabbits given ammonium chloride compared to those from rabbits receiving sodium bicarbonare.Based on these results,it was plausible that the change in the amount of this enzyme was related to the conditioning of bicarbonate transport in the collecting ducts.The amount Vol.31,No.1,1981 of enzyme also increased in the proximal straight tubule under these conditions , however,and,as we have seen,there is no detectable conditioning of bicarbonate absorption in this segment under the same treatment.In view of the lack of correlation between the glucose-6-phosphate dehydrogenase level and bicarbonate transport in the proximal tubules,the present results do not support the theory that the enzyme is directly involved in bicarbonate transport or its conditioning .…”
Section: Discussionmentioning
confidence: 98%
“…DIES and LOTSPEICH(1967)proposed,following an earlier suggestion by BRODSKY and CARASQUER(1952),that NADPH formed via the hexose monophosphate shunt might provide protons for acidification.Although they accepted the strong evidence favoring carbon dioxide as the source of most of the hydrogen ions secreted,they believed that such evidence did not preclude the existence of an additional secretory mechanism.In support of their theory they found that the level of glucose-6-phosphate dehydrogenase was elevated in the renal cortex of acidotic animals,but not in their livers.Their idea received further support from experiments by NORBY and SCHWARTZ(1978),who measured the rate of acidification by turtle urinary bladders.The turtle bladder acidifies its contents in vitro by a process that requires metabolism.Norby and Schwartz examined several different situations in which the rate of acidification was altered and found that the rate of acidification correlated with the rate of glucose metabolism via the hexose monophosphate shunt,but not with the rate of glycolysis. Schwartz et al(unpublished observation)measured glucose-6-phosphate dehydrogenase activity in isolated cortical collecting ducts and found that it was increased more than three-fold in tubules from rabbits given ammonium chloride compared to those from rabbits receiving sodium bicarbonare.Based on these results,it was plausible that the change in the amount of this enzyme was related to the conditioning of bicarbonate transport in the collecting ducts.The amount Vol.31,No.1,1981 of enzyme also increased in the proximal straight tubule under these conditions , however,and,as we have seen,there is no detectable conditioning of bicarbonate absorption in this segment under the same treatment.In view of the lack of correlation between the glucose-6-phosphate dehydrogenase level and bicarbonate transport in the proximal tubules,the present results do not support the theory that the enzyme is directly involved in bicarbonate transport or its conditioning .…”
Section: Discussionmentioning
confidence: 98%
“…More recently Norby and Schwartz have suggested that the pentose pathway is the major donor of energy to the H § pump [14]. These latter results were obtained by comparing the 14CO2 produced from 1-1~C-glucose to that produced from 6-t4C-glucose.…”
Section: Discussionmentioning
confidence: 99%
“…They postulated that this increased enzyme activity supported the increased rate of urinary acidification by a redox pump in the renal tubules. Norby and Schwartz (1978) observed in turtle urinary bladder that the rate of glucose metabolism by the pentose phosphate pathway is related to the rate of H + transport. The nature of the coupling between metabolism and pump rate remains, however, uncertain.…”
Section: A Redox Pumpsmentioning
confidence: 99%